Pengaruh Pengumuman Perubahan Harga BBM terhadap Abnormal Return dan Trading Volume Activity pada Perusahaan-Peruasahaan yang Tergabung dalam Kelompok LQ 45 Dibursa Efek Indonesia periode 2015-2016 - Denny Asmas (Universitas Batanghari Jambi, 2018)
The increase in the price of Fuel (BBM) can zoom in on the burden of the community and the business world. Vice versa, the drop in the price of fuel not only lighten the load of the community but also for the business world. Announcements containing information (information content), expected the market will react at the time the announcement was welcomed by the market. Market reaction is indicated by the existence of changes in prices of the securities in question. This research was conducted to find out whether there are abnormal return there is a difference, the difference in stock trading volume activity, abnormal return of shares and trading volume of activity before and after the events of the increase in the price of fuel oil. This research is quantitative research by doing event study. The population in this research is the stocks category LQ-45 period of March 2015 to April 2016 with a sample of companies that have listed on the Group Index LQ 45 period November 2014 and March 2015 and don't do Corporate Action. The results of hypothesis testing of research it can be concluded that there is a significant difference between the Abnormal Return (AR) and Trading Volume Activity (TVA) and events before and after the events of rising fuel prices, then there is no a significant difference between the Abnormal Return (AR) and between Trading Volume Activity (TVA) and event announcements of events before and after the drop in the price of fuel.